On the Existence of (v, k, λ) Difference Sets with k<1250 and k−λ Is a Square. (15th May 2012) - Osifodunrin, Adegoke Solomon
Abstract : We combine Turyn's self-conjugacy result, variance technique, Dillon dihedral trick, and Sylow theorem to investigate the existence of (v, k, λ ) difference sets in which k − λ is a square and k < 1250 .